Studies About the Hydration of Hybrid “Alkaline-Belite” Cement - Sánchez-Herrero, M. J.; Fernández-Jiménez, Ana; Palomo, A. (Frontiers in Materials, 2019)
The mechanical performance of a hybrid cement containing 48 % fly ash, 48 % mineralised belite clinker, 1.5 % gypsum and 2.5 % Na2SO4 was analysed and the hydration products were identified. The findings showed that the newly designed cement met European standard EN 197-1 compositional, mechanical and setting time requirements (cement type IVB). The hydration products forming in this blended ‘alkaline-belite’ cement (as it was determined through XRD, 29Si and 27Al MAS NMR and electron microscopy) consisted in a mix of cementitious gels: C-(A)-S-H and N-(C)-A-S-H, which interacted and over time evolved toward the latter with no detriment to the mechanical strength developed by the cement.